2001
DOI: 10.1183/09031936.01.00065501
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of daytime continuous positive airway pressure titration in severe obstructive sleep apnoea

Abstract: Efficacy of daytime continuous positive airway pressure titration in severe obstructive sleep apnoea. J.C. Rudkowski, P. Verschelden, R.J. Kimoff. #ERS Journals Ltd 2001. ABSTRACT: The aim of this study was to evaluate manual nasal continuous positive airway pressure (nCPAP) titration during daytime polysomnography compared with conventional overnight titration for patients with severe obstructive sleep apnoea.Thirty-two patients who underwent daytime titration were retrospectively matched (for age, sex, body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
(27 reference statements)
1
13
0
Order By: Relevance
“…There was no significant difference in CPAP pressure between nPSG and dPSG. Furthermore, previous studies showed no significant differences in terms of treatment compliance, symptom improvement, or side effects between pressures selected using daytime or nighttime PSG [24]. These results indicate that dPSG is also useful for early initiation of CPAP therapy.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…There was no significant difference in CPAP pressure between nPSG and dPSG. Furthermore, previous studies showed no significant differences in terms of treatment compliance, symptom improvement, or side effects between pressures selected using daytime or nighttime PSG [24]. These results indicate that dPSG is also useful for early initiation of CPAP therapy.…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore, despite the adequate titration of CPAP, pressure changes will be required after dPSG titration [26]. Despite these limitations of dPSG, this method is still reliable for identifying patients with moderate to severe OSAS [19][20][21], and daytime CPAP titration is an appropriate procedure for the effective titration of CPAP [24,26].…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of our procedure was chronobiologically appropriate time slot when aPT was performed. In contrast to our method, the previous two studies (27,28) did the titration in the morning, and the one did not describe the time zone of their titration (29). Regarding the chronobiological change in the vigilance level, Lavie and Segal (30) demonstrated that sleep propensity was second highest in the early afternoon (i.e.…”
Section: Discussionmentioning
confidence: 85%
“…Most of the patients had their Bi-level PAP and new CPAP introduced during the daytime. There is evidence that PAP can be effectively introduced as a day care procedure [25] and this is routine practice in some UK centers. It is conceivable that the Bi-level device was not optimally set up.…”
Section: Discussionmentioning
confidence: 99%